African Union (AU), Second edition - Magliveras, Konstantinos D.; Naldi, Gino J. (Alphen aan den Rijn, The Netherlands : Kluwer Law International, B.V, 2018)
"The monograph proceeds logically from the organization's genesis and historical development to the structure of its membership, its various organs and their mandates, its role in intergovernmental cooperation, and its interaction with decisions taken at the national level. Its competence, its financial management, and the nature and applicability of its data and publications are fully described."--
Preface -- Transition from the OAU to the AU -- Objectives and principles -- Admission to and withdrawal from the AU : the amendment of the Constitutive Act : the question of unratified OAU/AU treaties -- Imposition of punitive measures by the AU -- Organs -- Privileges and immunities -- Finances -- Settlement of disputes -- Human rights -- Refugees -- Economic cooperation -- Environment -- Other areas of activity -- Cooperation on economic affairs -- Cooperation on matters of peace and security.
"this book was originally published as a monograph in the International Encyclopaedia of Laws/Intergovernmental Organizations."
Includes bibliographical references (pages 497-504) and index.
Keywords: African Union; African Union; African cooperation; African cooperation; Politics and government; Africa -- Politics and government; Africa